Jurisprudential issues related to the fear prayer by Imam Ibn Al-Salah Al-Shahzuri - Ahmed Jassim Halil Obaid, (Islamic Sciences Journal, 2024)
ABSTRACT Praise be to God, Lord. Worlds, and the best prayers and peace be upon the best of creation, Muhammad, may God bless him and grant him peace, and upon his family and companions. The good ones. This is a brief study related to (the jurisprudential issues related to the Fear Prayer by Imam Ibn al-Salah al-Shahrzuri) and the rulings related to it. It becomes clear through this research that the Fear Prayer is lawful in the Qur’an and Sunnah, and it is an act of worship that God Almighty has made obligatory upon all Muslims in order to alleviate their burden in the event of The intensity of fear, and it is a Sunnah established by the Messenger of God (peace and blessings be upon him), and the honorable companions unanimously agreed that it should be done and permissible, and its legitimacy will continue until the Day of Resurrection. Alleviating it, Glory be to Him. The importance of this research is evident in the jurisprudential issues included in it, so they should be read and studied, the opinions and sayings of the jurists of the sects must be known, and success is from God. This research consists of an introduction, two sections, a conclusion, and a list of sources and references. As for the introduction: it included: the importance of the topic, the researcher’s methodology, and the research plan. The first section: (The concept of fear prayer and its legitimacy) and consists of two topics. The second section: (Some jurisprudential issues related to the fear prayer) and consists of three issues.